Predictors of tumor progression of low-grade glioma in adult patients within 5 years follow-up after surgery - Yan, Zhiqiang; Wang, Jiang; Dong, Qiufeng; Zhu, Lian; Lin, Wei; Jiang, Xiaofan (Frontiers in Surgery, 2022)
Background Glioma originates from glial cells in the brain and is the most common primary intracranial tumor. This study intends to use a retrospective analysis to explore the factors that can predict tumor progression in adult low-grade gliomas, namely WHO II grade patients, within 5 years after surgery. Methods Patients with WHO grade II glioma who were surgically treated in our hospital from February 2011 to May 2017 were included. According to the inclusion and exclusion criteria, 287 patients were included in the final analysis. According to the results of the 5-year follow-up (including survival and imaging review results), patients were divided into progression-free group and progression group. Univariate and multivariate analysis and related factors of tumor progression during the 5-year follow-up. Receiver operation curve (ROC) analyzes the best boundary value of quantitative treatment to distinguish high and low risks. Kaplan-Meier survival curve analysis of the predictive value of risk factors for patients' 5-year follow-up results. Results The results of the 5-year follow-up showed that 122 (42.5%) cases had no progress (progression free group, PFG), 165 (57.5%) cases had progress (progression group, PG), of which 97 (33.8%) cases were operated again, non- There were 41 (14.3%) surgical treatments, 34 (11.8%) all-cause deaths, and 27 (9.4%) tumor-related deaths. Univariate and multivariate analysis showed that age>50 years old (OR=1.42, 95% CI: 1.02-3.33, P=0.013), partial tumor resection (OR=1.86, 95% CI: 1.13-3.02, P=0.027), Tumor diameter>5cm (OR=1.85, 95% CI: 1.18-4.21, P=0.022) and long-term preoperative statin medication (OR=0.36, 95% CI: 0.15-0.84, P=0.036), etc., and 5 Closely related to progress during the annual follow-up. The Kaplan-Meier survival curve showed that the 5-year follow-up results were poor for ages >50 years, partial resection of tumors, and tumor diameters >5cm. The 5-year prognosis of long-term use of statins before surgery was relatively good. Conclusion Age> 50 years old, partial tumor resection, tumor diameter> 5 cm, and long-term preoperative use of statins are closely related to the 5-year prognosis after surgery.